The role of information for recognising business opportunities - Lutar-Skerbinjek, Andreja (Organizacija (Kranj), 2008)
For decision making and recognising business chances, managers need a lot of knowledge and information. They can get them on different ways. Vital part of information represents accounting information amongst which creditworthiness information of business partners and competitors has special role. They include information from annual reports and a lot of other information. Creditworthiness information could contain nonaccounting information, as well. The fastest and the cheapest way of getting information is on the Internet. Searching for information about different businesses on their internet pages could be a time-consuming work, so there are very useful data bases which contained information of majority of businesses in the country. On the Internet we could find quite a lot of such data basses, which contain more or less appropriate information. In this paper we discuss the importance of knowledge and information for recognising business chances and analysing appropriateness of accounting information, which can be obtained from five of the most widely used data bases which contain information about Slovene and Croatian businesses, for the estimation of creditworthiness of businesses.
Keywords: računovodstvo; računovodske informacije; podatki; pridobivanje; podatkovne baze